Informality in the Mypes and its influence in the collection of the General Sales Tax - Mostacero Mayo, Dany (2018)
The investigation explains the existence of influence of the informality dimension of the MYPES in the collection of the VAT, during the period 2010-2014, and why the informality of the Mypes was a factor that influenced the collection of VAT. In the period 2010-2014, based on this objective, a descriptive - explanatory analysis was carried out on the relationship between the variables, using official data from the Ministry of Production, Ministry of Labor, Sunat, among others. The main result shows that there is an Influence of the informality dimension of the MYPES in the Collection of the IGV in the period 2010-2014 and that the degree of this influence is statistically significant. In this way, it was concluded that the informality presented in the Mypes, significantly affects the collection of the VAT. And consequently, the tax revenues of the central government and is the main barrier to achieve the much-needed expansion of the tax base. In addition, informality is one of the problems that the government has not been able to solve, the figures indicate that these are even above the companies that operate in compliance with internal regulations. And while these types of companies create favorable scenarios for attracting labor, they generate severe distortions that contribute nothing to the development process.